Compressive strength, flexural strength and thermal conductivity of autoclaved concrete block made using bottom ash as cement replacement materials - Wongkeo W. (2014)
The bottom ash (BA) from Mae Moh power plant, Lampang, Thailand was used as Portland cement replacement to produce lightweight concrete (LWC) by autoclave aerated concrete method. Portland cement type 1, river sand, bottom ash, aluminium powder and calcium hydroxide (Ca(OH)2) were used in this study. BA was used to replace Portland cement at 0%, 10%, 20% and 30% by weight and aluminium powder was added at 0.2% by weight in order to produce the aerated concrete. Compressive strength, flexural and thermal conductivity tests were then carried out after the concrete were autoclaved for 6h and left in air for 7days. The results show that the compressive strength, flexural strength and thermal conductivity increased with increased BA content due to tobermorite formation. However, approximately, 20% increase in both compressive (up to 11.61MPa) and flexural strengths (up to 3.16MPa) was found for mixes with 30% BA content in comparison to just around 6% increase in the thermal conductivity. Thermogravimetry analysis shows C-S-H formation and X-ray diffraction confirm tobermorite formation in bottom ash lightweight concrete. The use of BA as a cement replacement, therefore, can be seen to have the benefit in enhancing strength of the aerated concrete while achieving comparatively low thermal conductivity when compared to the results of the control Portland cement concrete. © 2011 Elsevier Ltd.